New Product Development and Industrial Competitiveness in Industrial Sectors : A Systematic Literature Review - Faten Shahin; Zurina Kefeli@ Zulkefli (Brabdo for Educational Services, 2024)
Humanities and Natural Sciences Journal Volume 4. Issue 8 (page: 102-112)